Recurrent Word Combinations in EAP Test-Taker Writing: Differences between High- and Low-Proficiency Levels. Issue 1 (2nd January 2016) - Appel, Randy; Wood, David
ABSTRACT: The correct use of frequently occurring word combinations represents an important part of language proficiency in spoken and written discourse. This study investigates the use of English-language recurrent word combinations in low-level and high-level L2 English academic essays sourced from the Canadian Academic English Language (CAEL) assessment. Quantitative and qualitative measures of analysis were used to investigate how L2 English writers of differing proficiency levels made use of recurrent word combinations in their writing. Results indicate that low-level writers tend to use more stance and discourse-organizing expressions in their essays, and more of these identified expressions also appear in the articles included as part of the test materials (i.e., suggesting that low-level writers used verbatim copying as a test-taking strategy). High-level writers were found to be less dependent on the included reading articles and made greater use of referential bundles in their writing.